2015
DOI: 10.1038/ncb3129
|View full text |Cite
|
Sign up to set email alerts
|

EARP is a multisubunit tethering complex involved in endocytic recycling

Abstract: Recycling of endocytic receptors to the cell surface involves passage through a series of membrane-bound compartments by mechanisms that are poorly understood. In particular, it is unknown if endocytic recycling requires the function of multisubunit tethering complexes, as is the case for other intracellular trafficking pathways. Herein we describe a tethering complex named Endosome-Associated Recycling Protein (EARP) that is structurally related to the previously described Golgi-Associated Retrograde Protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
156
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(169 citation statements)
references
References 64 publications
10
156
0
1
Order By: Relevance
“…In contrast, depletion of protein components of the Retromer complex (45) inhibited VACV spread to a lesser extent, suggesting that a specific set of transport factors are needed. Recently, the EARP complex was described, in which the VPS54 component of GARP is replaced by the coil-coil domain-containing 132 protein (CCDC132, also called syndetin) (26). Functionally, EARP is required for endosome recycling back to the membrane, while GARP is needed for endosome-to-Golgi trafficking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, depletion of protein components of the Retromer complex (45) inhibited VACV spread to a lesser extent, suggesting that a specific set of transport factors are needed. Recently, the EARP complex was described, in which the VPS54 component of GARP is replaced by the coil-coil domain-containing 132 protein (CCDC132, also called syndetin) (26). Functionally, EARP is required for endosome recycling back to the membrane, while GARP is needed for endosome-to-Golgi trafficking.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial (Shiga and cholera) and plant (ricin and abrin) toxins (20) as well as some nonenveloped viruses, including simian virus 40 (SV40), polyomavirus, adeno-associated virus, and papillomavirus (21)(22)(23)(24), exploit the retrograde path to enter cells. Retrograde transport is highly selective and depends on numerous tethering factors, small GTPases, and SNARES (25,26). The small molecule Retro-2 interferes with retrograde transport from early endosome to the TGN specifically and protects against ricin and Shiga-like toxins (27) and virus entry (22)(23)(24), while having little or no apparent cellular toxicity.…”
mentioning
confidence: 99%
“…5) where TGFBRAP1 in CORVET would have to release VPS11, thereby allowing VPS11 to bind VPS39 and recruit the entire HOPS complex to RAB7-RILP during RAB5 (EEs) to RAB7 (LE) conversion. Specific targeting of tethering complexes by modulation of targeting subunits was recently also shown for GARP and EARP tethering on Golgi and EEs, respectively, indicating this might be a common mechanism in the regulation of vesicular fusion (43). TGFBRAP1 to VPS39 exchange might further be regulated by proteins such as MON1-CCZ1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Schindler et al (2015) recently showed that several components of this complex, including VPS52, also take part in a complex involved in endosome to plasma membrane trafficking, pointing to different functions of GARP-complex proteins in cellular trafficking. Although the role of VPS52 in plant cellular trafficking is not well understood, this protein was previously shown to localize to post-Golgi and prevacuolar compartments, suggesting it may have similar functions in trafficking as in other systems (Lobstein et al, 2004;Guermonprez et al, 2008).…”
Section: Discussionmentioning
confidence: 99%